(3cJGH aj GdWdhY hGdZQhHs - (3GhWhdhbSs
(3ChdgG (B:s
(3abGd HYV WdhYGJ GdchGcH hZQhHgG hNUhUkG jWdY GdchcH YfO WdhY GdTeS hGdZQhH s
(3BNQgG (B:s
(3hPdc eG CQOfG BNQ GdebGdI GdKGfjI hJe HJeGegG cJGH ChWhdhbS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1435s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs